The Effectiveness of the Use of Aldiko Book Reader in Indonesian Language Learning for Natural Sciences - Usman M; Sam Hermansyah (Journal of Paddisengeng Technology, 2025)
Background. The use of technology in education is one way to improve the quality of learning. One of the applications used for learning is Aldiko Book Reader, which is expected to help students understand the learning material. This study was conducted to measure the effectiveness of the use of Aldiko Book Reader in Indonesian language learning at SMA Negeri 1 Sidrap, especially for students in grade XI Natural Sciences (IPA) 1. Purpose. This study aims to explain the effectiveness of the use of Aldiko Book Reader in Indonesian learning for students in grade XI Science 1 SMA Negeri 1 Sidrap. Method. This study is a quantitative research with a population of 35 students in class XI Science 1 SMA Negeri 1 Sidrap and a sample of 25 students. The data collection techniques used are documentation, tests, and questionnaires. The collected data was then processed using an effectiveness test measured based on four indicators. Results. The results of the study show that the use of Aldiko Book Reader is effective in learning Indonesian. Of the four indicators of effectiveness, all of them qualified. First, the average score of students after using Aldiko Book Reader increased (68.5 < 82.5). Second, the average score of students after using the application is 82.5, which is above the KKM standard (70). Third, the average score of student gain is 54.8, which is in the high category. Fourth, the completeness of classical learning reaches 100%. Conclusion. Based on the results of the study, it can be concluded that the use of Aldiko Book Reader is effective in improving the Indonesian learning outcomes of students in grade XI Science 1 SMA Negeri 1 Sidrap, as evidenced by the significant increase in student scores and test scores.